2021
DOI: 10.1177/1078390321999725
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Factors Associated With Burnout in Intensive Care Nurses: A Cross-Sectional Study

Abstract: BACKGROUND: Although previous studies have separately revealed that parameters such as anxiety, depression, and secondary traumatic stress (STS) are associated with burnout, there is still a limited understanding of the relationship between anxiety, depression, and STS and burnout in intensive care unit (ICU) nurses. AIMS: To investigate the relationship between levels of burnout, anxiety, depression, and STS in ICU nurses. METHOD: A cross-sectional study was conducted with ICU nurses ( N = 164) from a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…ICU nurses are presented with large number of highly complex patients requiring vigilant monitoring and interventions. Continuous exposure to unpredictable conditions, in addition to demands of caring for unstable patients and a distressed family, places ICU nurses at high risk of anxiety, stress, fatigue, and burnout, which all are significant predictors of depression 54‐56 . Further research is required to identify effective interventions for preventing and managing depression among nurses in ICU settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICU nurses are presented with large number of highly complex patients requiring vigilant monitoring and interventions. Continuous exposure to unpredictable conditions, in addition to demands of caring for unstable patients and a distressed family, places ICU nurses at high risk of anxiety, stress, fatigue, and burnout, which all are significant predictors of depression 54‐56 . Further research is required to identify effective interventions for preventing and managing depression among nurses in ICU settings.…”
Section: Discussionmentioning
confidence: 99%
“…ing for unstable patients and a distressed family, places ICU nurses at high risk of anxiety, stress, fatigue, and burnout, which all are significant predictors of depression [54][55][56]. Further research is required to identify effective interventions for preventing and managing depression among nurses in ICU settings.T A B L E 2…”
mentioning
confidence: 99%
“… 24 In Yıldız’s study, which examined the psychopathological factors associated with burnout in 164 intensive care nurses, it was established that the depression and secondary traumatic stress scores were high and explained 61% of the burnout levels of the nurses. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies have indicated that nurses have high rates of anxiety and depression, often linked to occupational stress. [13][14][15] A recent study of the mental health characteristics of nurses who died by suicide found nurses being more likely than nonnurses to report a mental health problem and more likely to have a specific diagnosis of depression prior to death. 5 While not considered a mental illness per se, burnout has been reported within the nursing profession to range from 33% 16 to 50%.…”
Section: Mental Health and Nurse Suicidementioning
confidence: 99%